2016
DOI: 10.14238/sp6.4.2005.159-65
|View full text |Cite
|
Sign up to set email alerts
|

Hipertensi pada Remaja

Abstract: Pengukuran tekanan darah saat pemeriksaan kesehatan rutin terhadap remaja akan memungkinkan ditemukannya hipertensi asimptomatik yang signifikan oleh karena penyakit yang tidak diketahui, dan memperkuat pernyataan bahwa sering terjadi kenaikan tekanan darah yang ringan pada remaja. Penyebab hipertensi pada remaja (usia 13-18 tahun) yang paling sering adalah hipertensi esensial (80%), diikuti penyakit ginjal. Hipertensi esensial pada remaja dapat merupakan lanjutan dari masa kanak-kanak dan berlanjut ke masa de… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
12
0
34

Year Published

2017
2017
2019
2019

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 33 publications
(47 citation statements)
references
References 15 publications
1
12
0
34
Order By: Relevance
“…4 Less than 5% of the children, with the majority of them was adolescent, were affected by hypertension in one blood pressure measurement. 1,3 In Indonesia, the rate of the incidence of hypertension in children and adolescents was reported to be 3.55-4.6%. 1 In our study of 240 adolescents, 30 (12.55%) had high blood pressure.…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…4 Less than 5% of the children, with the majority of them was adolescent, were affected by hypertension in one blood pressure measurement. 1,3 In Indonesia, the rate of the incidence of hypertension in children and adolescents was reported to be 3.55-4.6%. 1 In our study of 240 adolescents, 30 (12.55%) had high blood pressure.…”
Section: Discussionmentioning
confidence: 99%
“…1,3 In Indonesia, the rate of the incidence of hypertension in children and adolescents was reported to be 3.55-4.6%. 1 In our study of 240 adolescents, 30 (12.55%) had high blood pressure. Subjects' mean age was 14.7 (SD 0.9) years, which indicated that high blood pressure had probably not yet been detected.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations